A preliminary index of SARS-CoV-2 diagnostic testing patents - Dimitrios Mavridis; Zoltán Cséfalvay; Petros Gkotsis; Lesley Potters (European Commission, Joint Research Centre (JRC), 2021)
Diagnostic testing for COVID-19 is an important part of the management of the pandemic. A diagnostic testbased policy response assumes the existence of diagnostic kits on a large scale, their availability at the point of care, an efficient way to administer the tests to the economically and socially active population, and the analysis and communication of the results. Overall, information produced by a diagnostic testing strategy is a key input to individual and public health decision making. In this paper, we attempt to answer the question of where knowledge prerequisites to produce SARS-CoV-2 diagnostic tests are located in the world. We compile background knowledge on virology, particularly concerning the various options of diagnostic testing for known Coronaviruses with information retrieved from the corpus of patent documents. More specifically, we extract keywords from this field of expertise and we query these keywords in patent application filings. We construct an indicator of inventive activity in the area of Coronavirus diagnostic tests, and we decompose it across several dimensions - time, location of inventors, and thematic classifications. Our reasoning is that previous knowledge in the field might prove crucial for the development and deployment of diagnostics for SARS-CoV-2. In the current pandemic, the knowledge prerequisites for the production of diagnostic tests are pertinent to a wide range of issues. The knowledge that is encapsulated in the patenting activity, which we document, can potentially be far-reaching if it becomes widely available to the scientific and industrial actors engaged in applied biomedical research. We present, without evaluating, a number of policy options.
Keywords: 330